2008
DOI: 10.1007/s11069-008-9234-6
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative appraisal of earthquake hazard parameters computed from Gumbel I method for different regions in and around Turkey

Abstract: Useful information concerning the earthquake hazard parameters distributed in Turkey and the adjacent areas are estimated in the present work. Based on Gumbel's I distribution parameters we are able to estimate the hazard values of the investigated area which are the mean return periods, the most probable maximum magnitude in the time period of t-years and the probability for an earthquake occurrence of magnitude CM during a time span of t-years. Figures concerning the spatial distribution of probabilities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…These constants can also be estimated with the help of famous Gutenberg and Richter relationship (1956) and related to its constants a and b by equations a = (ln a/ln 10) and b = (b/ln10). However, the constants, estimated using approach of Gumbel's extreme value distribution, are more significance and they are better related to the tectonics of the study region (Makropoulos and Burton 1984;Tsapanos and Burton 1991;Ö ztrürk et al 2008). A plot of largest annual magnitude (m) versus observed probability (G) estimated by three approaches can be seen in Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…These constants can also be estimated with the help of famous Gutenberg and Richter relationship (1956) and related to its constants a and b by equations a = (ln a/ln 10) and b = (b/ln10). However, the constants, estimated using approach of Gumbel's extreme value distribution, are more significance and they are better related to the tectonics of the study region (Makropoulos and Burton 1984;Tsapanos and Burton 1991;Ö ztrürk et al 2008). A plot of largest annual magnitude (m) versus observed probability (G) estimated by three approaches can be seen in Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Nordquist (1945) attempted this theory first time for the earthquakes in southern California and for the largest earthquakes in the world. After that a number of researchers of the world applied this method in different regions (Gayskiy and Katok 1965 in Soviet Union;Epstein and Lomnitz 1966 in America;Dick 1965 in New Zealand;Milne and Devenport 1969 in Canada;Hubernova 1968 andSchenkova andKarnik 1970 in Europe;Shakal and Willis 1972 in North Circum-Pacific seismic belt; Rao and Rao 1979;Goswami and Sarmah 1983;Singh 1997 andShanker et al 2007 in India and adjoining region; Bayrak et al 2005 andÖ ztrürk et al 2008 for Turkey region).…”
Section: Introductionmentioning
confidence: 99%
“…Bayrak et al [30] evaluated the seismicity and earthquake hazard parameters of Turkey based on maximum regional magnitude. Öztürk et al [31] estimated the mean return periods, the most probable magnitude in a time period of t-years, and the probability of earthquake occurrence for a given magnitude during a time span of t-years for different regions in and around Turkey. They also showed that in the specific region, the most probable earthquake magnitude in the next 100 years would be over 7.5.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There exist a lot of regional and temporal studies on the space-time characteristics of earthquake activity for different parts of the world, and many authors obtained important outcomes and conclusions by using scaling laws (e.g., Utsu, 1971;Mandelbrot, 1982;Habermann, 1983;Hirata, 1989;Frohlich and Davis, 1993;Wiemer and Wyss, 2000;Awad, 2005;Öztürk et al, 2008;Öncel and Wilson, 2007;Roy et al, 2011;Öztürk, 2011;Ali, 2016). The Albania region is seismically active with tens of destructive large earthquakes over the past twenty centuries as revealed from the historical sources (Sulstarova et al, 1980;Ormeni, 2010).…”
Section: Introductionmentioning
confidence: 99%